2020
DOI: 10.3390/su12020520
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Determinants of Food Security in the Areas of the Nam Theun2 Hydropower Project in Khammuan, Laos

Abstract: This article examines the driving forces of food security in the areas of the Nam Theun2 Hydropower Project (NT2) in Khamuan, Laos. A questionnaire survey was conducted to collect data from 100 NT2 resettlement households based on the random sampling technique. A linear regression technique was used to identify the influence of household food insecurity. The result showed that household size, food price, drought, shock, household income per month, number of laborers, gender of the household head, and farmland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
3
4
0
Order By: Relevance
“…Other things being constant, one unit of incremental change in household size increases the risk of household food insecurity by almost 1.604-fold. This finding is consistent with studies [15][16][17]47], but in contrast with the findings of prior studies [43,45,56]. The potential explanation for this phenomenon is the combination of the current high unemployment rate, limited employment prospects, and low wage rates, resulting in an additional household member dividing already restricted resources, ultimately leading to household food insecurity.…”
Section: Factors Of Household Food Insecurity In Lideta Sub-city Addi...supporting
confidence: 90%
See 2 more Smart Citations
“…Other things being constant, one unit of incremental change in household size increases the risk of household food insecurity by almost 1.604-fold. This finding is consistent with studies [15][16][17]47], but in contrast with the findings of prior studies [43,45,56]. The potential explanation for this phenomenon is the combination of the current high unemployment rate, limited employment prospects, and low wage rates, resulting in an additional household member dividing already restricted resources, ultimately leading to household food insecurity.…”
Section: Factors Of Household Food Insecurity In Lideta Sub-city Addi...supporting
confidence: 90%
“…The results of the study indicate that households led by men exhibit a greater level of food insecurity as compared to those led by women. This finding resonates with the previous study conducted in Dire Dawa city, Ethiopia, and Kindo Didaye District, Southern Ethiopia [50,51] but against other evidence [15,[52][53][54]. The observed difference can plausibly be attributed to variations in socio-economic factors across study areas and the progression of female empowerment in the spheres of professional employment and strategic influence [55].…”
Section: Factors Of Household Food Insecurity In Lideta Sub-city Addi...supporting
confidence: 87%
See 1 more Smart Citation
“…Mathematical models have been extensively used in research into household severe food insecurity dynamics because they play an important role in improving our understanding of major factors contributing to the household severe food insecurity dynamics. These models range from logistic regression 25 – 29 , linear regression model 30 , 31 , generalized linear mixed-effects models 32 , 33 , generalized estimating Equations 34 , 35 , to additive model 36 . However, these classical modelling approach, without considering spatial effect, affects statistical inference in many ways.…”
Section: Introductionmentioning
confidence: 99%
“…These variations of food security are influenced by demographic factors (age, gender, marital status, family size, and dependency ratio), economic factors (farm input, land size, livestock ownership, credit access, membership, and extension access), farm income, and non-agricultural income flood, farm diseases, and war; these factors affect food insecurity through the agricultural production channels and rural income [32][33][34][35]. The magnitude and direction of the association among these parameters and farming households' food insecurity vary across studies [3,24,[34][35][36][37][38]. For example, a study was conducted on household food insecurity in East Africa by Gebre and Rahut [4], and results indicated that age of a head of household, family size, and crop loss, are positively significant, and education level, household income, borrowing money from informal and formal, group members, and livestock unit are negatively associated with prevalent household food insecurity.…”
Section: Introductionmentioning
confidence: 99%